Dry-method electrode membrane and preparation method thereof, electrode and battery

By adopting different temperature shearing methods in the dry electrode process, the mixing uniformity and fibrosis of the polytetrafluoroethylene binder are improved, the problem of low electrode film strength is solved, and higher tensile strength and lower binder content is achieved.

CN119725367AActive Publication Date: 2025-03-28EVE ENERGY CO LTD

Patent Information

Application Number
CN202411922353.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-03-28
Estimated Expiration
2044-12-24

AI Technical Summary

Technical Problem

In the dry electrode process, the polytetrafluoroethylene binder is unevenly mixed and the degree of fibrosis is low, resulting in low electrode film strength.

Method used

Using different temperature shearing methods, low-temperature and high-speed shearing is performed first to reduce the particle size of the binder to the nanometer level and the distribution is more uniform. Then high-temperature and high-speed shearing is performed to make the binder fibrosis more, and a dry electrode film is prepared.

Benefits of technology

The tensile strength of the electrode film is improved, the use content of the binder is reduced, the anisotropy after film formation is reduced, and it is suitable for electrode production of different thicknesses.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119725367A_ABST
    Figure CN119725367A_ABST
Patent Text Reader

Abstract

The invention discloses a dry-method electrode film and a preparation method thereof, an electrode and a battery, and belongs to the technical field of batteries. The method comprises the following steps: mixing polytetrafluoroethylene, an active substance and a conductive agent, and crushing to obtain a crushed mixture; performing primary airflow grinding and shearing on the crushed mixture to obtain a ground and sheared mixture; the primary shearing conditions are as follows: the airflow temperature is-10 to 10 DEG C, the airflow pressure is 0.7 to 0.9 MPa, and the rotating speed is 8000 to 12000 rpm; carrying out secondary airflow grinding, shearing and fibration on the ground and sheared mixture to obtain a fibration material; and carrying out secondary fibration treatment on the fibration material to obtain the dry-method electrode film. The method can significantly improve the tensile strength of the electrode film, improve the liquid absorption rate of the electrode and reduce the resistivity of the electrode.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of battery technology, and in particular to a dry electrode membrane and a preparation method thereof, an electrode and a battery. Background Art

[0002] Traditional lithium battery electrodes are usually prepared by a coating method. First, a binder, solvent and conductive agent are configured into a conductive slurry, and then electrode active materials are added in batches to form a uniform slurry. Finally, the slurry is evenly coated on the current collector through a coating device, and then dried, rolled and cut into pole pieces. This method has high requirements on the dispersion of the conductive agent, the viscosity control of the slurry and the coating equipment. The pole pieces have a low content of active materials, the production process is strictly controlled, and thick pole pieces cannot be produced. In addition, the solvent drying and solvent recovery processes consume a lot of energy and have high costs, which is not environmentally friendly.

[0003] In order to solve the above problems, a dry electrode process has been developed. The main steps of this process are to mix the conductive agent, binder, and electrode active material evenly, and then fiberize the binder PTFE through high-speed shearing to form a fiber network to bind the active material and the conductive agent, and finally further fiberize it through rolling to form a self-supporting electrode membrane and coat it on the current collector to obtain a double-sided electrode. Among them, the fiberization step is the key step of the dry electrode process. It is necessary to use a huge shear force to evenly disperse and fiberize the PTFE. The mainstream methods include air flow shearing, high-speed stirring shearing, ball milling shearing, etc., but the conventional fiberization process requires a high binder content (such as more than 8wt%), a high degree of binder fiberization, a high shear force requirement for the equipment, and a high uniformity requirement for the mixed material. The production time is long, and it is difficult to achieve large-scale production. The main reason for this contradiction is the special properties of PTFE, the binder required by the process. The electrode membrane molding of this process requires PTFE to be evenly dispersed between the electrode materials and to form a nano-scale fiber network through shearing and stretching. The higher the molecular weight of PTFE, the easier it is for the fiberization process to occur. However, the high molecular weight PTFE on the market needs to avoid agglomeration during transportation, and is often made into particles with a secondary particle size of 500-700μm. For positive electrode active materials with a particle size generally less than 30μm and conductive agents with nano-scale particle size, it is easy to cause segregation due to uneven mixing during the mixing process, resulting in uneven fiberization effect. Summary of the invention

[0004] The main purpose of the present application is to provide a dry electrode membrane and its preparation method, electrode and battery, so as to solve the problem of uneven mixing of polytetrafluoroethylene binder and low fiberization degree in the dry electrode process, which leads to low strength of electrode membrane.

[0005] In order to achieve the above object, according to one aspect of the present application, a method for preparing a dry electrode membrane is provided, the method comprising the following steps:

[0006] Step S1: mixing and crushing a polytetrafluoroethylene material, an electrode active material and a conductive agent to obtain a crushed mixture;

[0007] Step S2: performing a primary air flow grinding and shearing on the pulverized mixture to obtain a ground and sheared mixture; wherein the conditions for the primary air flow grinding and shearing include: an air flow temperature of -10°C to 10°C, a compressed air flow pressure of 0.7 to 0.9 MPa, and a shearing speed of 8000 to 12000 rpm;

[0008] Step S3: performing secondary airflow grinding and shearing fiberization on the ground and sheared mixture to obtain a fiberized material;

[0009] Step S4: performing secondary fiberization treatment on the fiberized material to obtain a dry electrode membrane.

[0010] Furthermore, the air flow temperature of the primary air flow grinding and shearing is -5°C to 5°C; further, 0 to 5°C.

[0011] Furthermore, the air flow temperature of the secondary air flow grinding and shearing is 50° C. to 100° C., the compressed air flow pressure is 0.7 to 0.9 MPa, and the shearing rotation speed is 8000 to 12000 rpm.

[0012] Furthermore, the air flow temperature of the secondary air flow grinding and shearing is 60-100°C; further, 70-100°C; further, 80-100°C.

[0013] Furthermore, the shearing speed of the primary air flow grinding shearing is 10000-11000 rpm.

[0014] Furthermore, the shearing speed of the secondary airflow grinding and shearing is 10000-11000 rpm.

[0015] Furthermore, the polytetrafluoroethylene material is a polytetrafluoroethylene dispersed resin, the average particle size of which is 400-600 μm, the molecular weight of which is 500,000-8 million, and the compression ratio of which is 100-3000.

[0016] Furthermore, the polytetrafluoroethylene dispersion resin is kept at -8°C to -12°C for 8 to 12 hours before mixing.

[0017] Furthermore, the specific process of step S1 includes: mixing and crushing the electrode active material and the conductive agent to obtain powder A; mixing and crushing the heat-insulated polytetrafluoroethylene dispersion resin and the powder A to obtain a crushed mixture.

[0018] Furthermore, the electrode active material and the conductive agent are mixed by a ball mill or a high-speed mixer, and the rotation speed of the high-speed mixer is 400-600 rpm.

[0019] Furthermore, the ball-to-material ratio of the ball mill is 1:(1-2).

[0020] Furthermore, the polytetrafluoroethylene dispersion resin and the powder A are mixed by a double-motion mixer or a three-dimensional motion mixer.

[0021] Furthermore, the mixing time of the polytetrafluoroethylene dispersion resin and the powder A in the double-motion mixer is 20 to 40 minutes.

[0022] Furthermore, the average particle size of the pulverized mixture is 8 to 12 μm.

[0023] Furthermore, the average particle size of the ground and sheared mixture is 3 to 6 μm.

[0024] Furthermore, the first air flow grinding and shearing and / or the second air flow grinding and shearing adopts an air flow grinder.

[0025] Furthermore, the air flow mill is a fluidized bed air flow mill.

[0026] Furthermore, the secondary fiberization treatment uses a differential speed roller press to perform differential speed fiberization.

[0027] Furthermore, the rolling temperature of the differential roller press is 60°C to 120°C, and the rolling speed ratio is 1:(1 to 1.5).

[0028] Furthermore, the weight ratio of the electrode active material to the conductive agent is (90-95):(0-5).

[0029] Furthermore, the weight ratio of the powder A to the heat-insulated polytetrafluoroethylene dispersion resin is (95-99):(1-3).

[0030] Furthermore, the electrode active material includes a positive electrode active material and a negative electrode active material; wherein the positive electrode active material is selected from at least one of lithium iron phosphate, lithium manganese iron phosphate, lithium nickel cobalt manganese oxide, lithium cobalt oxide, lithium manganese oxide, lithium nickel cobalt aluminum oxide and manganese dioxide; the negative electrode active material is selected from at least one of artificial graphite, natural graphite, lithium titanate, silicon oxygen negative electrode material and silicon carbon.

[0031] Furthermore, the conductive agent is selected from at least one of conductive carbon black, graphite, graphene, carbon nanotubes, carbon fibers, acetylene black and Ketjen black.

[0032] According to a second aspect of the present application, a dry electrode membrane is provided, which is prepared by using the above-mentioned method for preparing the dry electrode membrane.

[0033] Furthermore, the thickness of the dry electrode film is 100-150 μm, the tensile strength is 0.2-0.4 MPa, and the compaction density is 2.50-3.30 g / cm 3 .

[0034] According to the third aspect of the present application, a method for preparing a dry electrode is provided, and the method for preparing a dry electrode comprises the following steps: rolling a dry electrode film onto at least one side of a current collector; wherein the dry electrode film is the above-mentioned dry electrode film.

[0035] Furthermore, the temperature of the rolling is 0°C to 100°C.

[0036] Furthermore, the current collector is selected from at least one of copper foil, carbon-coated copper foil, aluminum foil, nickel foil, stainless steel mesh, aluminum mesh and nickel mesh.

[0037] According to a fourth aspect of the present application, a battery is provided, comprising an electrode, a separator and an electrolyte; the electrode is an electrode prepared by the above-mentioned dry electrode preparation method.

[0038] The technical solution of this application is applied to provide a method for preparing a dry electrode membrane. Based on the phase change temperature of the binder PTFE, different temperature shearing methods are adopted. First, low-temperature high-speed shearing is performed to reduce the binder particle size to the nanoscale and distribute it more evenly. Then, high-temperature high-speed shearing is performed to make the binder fiberized to a higher degree. The tensile strength of the prepared electrode membrane is higher, the content of the binder is less, and the anisotropy after film formation is reduced. This method also breaks through the electrode thickness limit and can produce electrodes with a thickness of 30μm to 3mm, and is suitable for different battery systems. Compared with the traditional coating electrode process, the drying step is eliminated, the powder loss rate of the pole piece is reduced, and thick pole pieces can be produced to meet the manufacturing needs of higher energy density batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] The drawings constituting part of the present application are used to provide a further understanding of the present application. The exemplary embodiments and descriptions of the present application are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings:

[0040] Figure 1 The following is a flow chart of the preparation process of the dry electrode membrane and the electrode according to the embodiment of the present application;

[0041] Figure 2 The SEM image of PTFE coated on the surface of the positive electrode active material before fiberization in Example 1 of the present application is shown;

[0042] Figure 3 The SEM image of the PTFE fiberization effect in Example 1 of the present application is shown;

[0043] Figure 4 The SEM image of the surface of the electrode membrane in Example 1 of the present application is shown;

[0044] Figure 5A comparison chart of longitudinal tensile strength of electrode films of Example 1, Comparative Example 1, Comparative Example 2 and Comparative Example 3 of the present application is shown;

[0045] Figure 6 A comparison chart of the transverse tensile strength of the electrode films of Example 1, Comparative Example 1, Comparative Example 2 and Comparative Example 3 of the present application is shown;

[0046] Figure 7 A comparison chart of the electrode resistivity of Example 1, Comparative Example 1, Comparative Example 2, and Comparative Example 3 of the present application is shown;

[0047] Figure 8 A comparison chart of the liquid absorption rate of electrodes of Example 1, Comparative Example 1, Comparative Example 2 and Comparative Example 3 of the present application is shown. DETAILED DESCRIPTION

[0048] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present application will be described in detail below with reference to the accompanying drawings and in combination with the embodiments.

[0049] In the prior art, the PTFE binder fiberization usually adopts air flow shearing, high-speed stirring shearing, ball milling shearing and other methods. These methods require a relatively high amount of binder, such as more than 8wt%, and the secondary particle size of the PTFE used is 500-700μm. It is unevenly mixed with the active material and the conductive agent, which is easy to cause segregation and may produce uneven fiberization effect, thereby reducing the tensile strength and other properties of the dry electrode membrane. Therefore, based on the phase transition temperature of the binder PTFE, this application adopts a targeted shearing method at different temperatures to improve the mixing uniformity and fiberization degree of PTFE.

[0050] According to one aspect of the present application, a method for preparing a dry electrode membrane is provided, the method comprising the following steps:

[0051] Step S1: mixing and crushing a polytetrafluoroethylene material, an electrode active material and a conductive agent to obtain a crushed mixture;

[0052] Step S2: performing a primary air flow grinding and shearing on the pulverized mixture to obtain a ground and sheared mixture; wherein the conditions for the primary air flow grinding and shearing include: an air flow temperature of -10°C to 10°C, a compressed air flow pressure of 0.7 to 0.9 MPa, and a shearing speed of 8000 to 12000 rpm;

[0053] Step S3: performing secondary airflow grinding and shearing on the ground and sheared mixture to obtain a fiberized material;

[0054] Step S4: performing secondary fiberization treatment on the fiberized material to obtain a dry electrode membrane.

[0055] In the present application, the air flow temperature of the primary air flow grinding and shearing is selected from any value among -10℃, -9℃, -8℃, -7℃, -6℃, -5℃, -4℃, -3℃, -1℃, 0℃, 1℃, 2℃, 3℃, 4℃, 5℃, 6℃, 7℃, 8℃, 9℃, 10℃, or any range between two thereof; the air flow temperature of the secondary air flow grinding and shearing is selected from any value among 50℃, 55℃, 60℃, 65℃, 70℃, 75℃, 80℃, 85℃, 90℃, 95℃, 100℃, or any range between two thereof; for example, the primary air flow grinding temperature is -5 to 10℃, further -5 to 5℃, further 0 to 5℃, and for example 0℃; the secondary air flow grinding temperature is 50 to 100℃, further 60 to 100℃, further 70 to 100℃, further 80 to 100℃, and for example 80℃.

[0056] The shear speed of the primary air flow grinding and shearing in the present application is any value among 8000rpm, 8500rpm, 9000rpm, 9500rpm, 10000rpm, 10500rpm, 11000rpm, 11500rpm, 12000rpm, or a range value between any two of them; for example, 10000rpm; the shear speed of the secondary air flow grinding and shearing is any value among 8000rpm, 8500rpm, 9000rpm, 9500rpm, 10000rpm, 10500rpm, 11000rpm, 11500rpm, 12000rpm, or a range value between any two of them; for example, 10000rpm; the two shear speeds may be the same or different.

[0057] The preparation method of the dry electrode membrane provided in the present application is based on the phase transition temperature of the binder PTFE (the phase transition temperature of PTFE is 19°C), and adopts a different temperature shearing method. The PTFE-containing mixture is first subjected to low-temperature high-speed shearing to reduce the particle size of the PTFE binder from the micron level to the nanometer level, so that the dispersion of the mixture is more uniform; in the low-temperature high-speed shearing process, since the temperature is lower than the phase transition temperature, theoretically, PTFE will basically not undergo fiberization, but heat will be generated during the shearing process. If the preset fiberization effect is to be achieved, the above-mentioned low-temperature high-speed shearing temperature is controlled at -10 to 1 0℃ is suitable; since the shear rate and the shear rate of fiberization are similar, high-speed grinding and shearing are adopted, and the conventionally used PTFE with large particle size of micron level can be ground and sheared to nanometer level, and the PTFE is coated on the active material after being reduced to nanometer size; this will greatly improve the uniformity of mixing of various raw materials, and is more conducive to the subsequent fiberization of PTFE mixture; after the PTFE mixture is made into nanometer level and then subjected to high-temperature and high-speed shearing, the degree of PTFE fiberization is higher, the tensile strength of the prepared electrode membrane is higher, the content of binder used is less, and the anisotropy after membrane formation is also reduced.

[0058] The present application uses continuous dry rolling to make electrodes. The production process does not require the use of solvents and there is no drying process, which reduces production energy consumption. The present application allows the electrode binder to exist in a fibrous state, so that the positive electrode active material and the conductive agent particles are in closer contact, thereby increasing the electrode compaction density, reducing the electrode sheet resistance, and lowering the electrode sheet powder loss rate. The present application uses temperature to control the PTFE binder particle size and fiberization degree, thereby improving the uniformity of the mixture, reducing the difficulty of electrode film molding, and increasing the tensile strength of the film.

[0059] In some embodiments, the polytetrafluoroethylene material is a polytetrafluoroethylene dispersion resin having an average particle size of 400-600 μm, a molecular weight of 500,000-8 million, and a compression ratio of 100-3000.

[0060] The improved method of the present application is mainly aimed at the high molecular weight PTFE commonly used in the market, which needs to be made into large particles with a secondary particle size of 500-700 μm to avoid agglomeration during transportation; in the prior art, the large-particle PTFE is often directly mixed with active materials and conductive agents, resulting in the inability to mix micron-sized PTFE and other nano-sized materials well, thereby affecting the PTFE fiberization degree and electrode film strength. By adopting the improved method of the present application, micron-sized PTFE can be made into nano-sized PTFE, which can further improve its dispersion uniformity.

[0061] In some embodiments, the polytetrafluoroethylene dispersion resin is kept at -8°C to -12°C for 8 to 12 hours before mixing; for example, kept at -10°C for 10 hours. The purpose of keeping the PTFE at the above temperature before use is to prevent the PTFE from further agglomerating and increasing the particle size, thereby avoiding difficulties in subsequent powder mixing.

[0062] In some embodiments, the specific process of step S1 includes: mixing and crushing the electrode active material and the conductive agent to obtain powder A; mixing the heat-insulated polytetrafluoroethylene dispersion resin and the powder A to obtain a crushed mixture. The present application can further improve the mixing uniformity by a stepwise mixing method.

[0063] In some embodiments, the electrode active material and the conductive agent are mixed by a ball mill or a high-speed mixer, the rotation speed of the high-speed mixer is 400-600 rpm; the ball-to-material ratio of the ball mill is 1:(1-2); the polytetrafluoroethylene dispersion resin and powder A are mixed by a double-motion mixer or a three-dimensional motion mixer; the mixing time in the double-motion mixer is 20-40 min.

[0064] The present application selects different mixing equipment and process conditions according to different mixed materials, and specifically improves the dispersion and uniformity of each mixture; when PTFE and powder A are mixed in a double-motion or three-dimensional motion mixer, the mixing time is controlled as mentioned above, 20 to 40 minutes, for example, 30 minutes; excessive shearing can be avoided, which causes the PTFE to fiberize before the subsequent high-temperature and high-speed shearing, which is not conducive to the subsequent PTFE fiberization effect.

[0065] In some embodiments, the average particle size of the crushed mixture is 8-12 μm; the average particle size of the ground and sheared mixture is 3-6 μm, for example 3-4 μm. The present application gradually reduces the particle size of the mixture through the crushing and grinding and shearing processes, which is helpful for the subsequent airflow grinding and shearing process.

[0066] In some embodiments, the first air flow grinding and shearing and / or the second air flow grinding and shearing adopts an air flow grinder; for example, a fluidized bed air flow mill is adopted. The present application adopts the above equipment in the two grinding and shearing. Compared with a mixer or a ball mill, the heat generated by the air flow mill during the grinding process will be taken away in time by the low-temperature air flow, avoiding deformation, fiberization, and uneven distribution of PTFE due to local heat accumulation in the equipment cavity. In the fiberization process, a high-temperature air flow (specifically, an air flow above the phase change temperature of PTFE, i.e., above 19°C) can be used to make the PTFE undergo a phase change and promote the fiberization of PTFE. When the temperature is lower than 19°C, the PTFE molecular chain is a 13 / 6 spiral, and a phase change occurs at 19°C, and the molecules are slightly untied to form a 15 / 7 spiral, which is easier to fiberize.

[0067] In some embodiments, the secondary fiberization treatment uses a differential speed roller press for differential fiberization; the roller pressing temperature can be 60°C to 120°C, and the roller pressing speed ratio can be 1:(1 to 1.5). The above roller pressing conditions are used in this application to fully and completely fiberize the PTFE mixture and form an electrode membrane.

[0068] In some embodiments, the weight ratio of the electrode active material to the conductive agent is (90-95): (0-5), for example, 92: 5; the weight ratio of the powder A to the polytetrafluoroethylene dispersion resin after heat preservation is (95-99): (1-5), for example, 98: 2. In the present application, the content of PTFE is controlled at 1-5, and the fiberization is performed after mixing with other components to achieve a better synergistic effect, thereby avoiding the phenomenon of cracks in the diaphragm due to excessive or insufficient PTFE content.

[0069] In some embodiments, the electrode active material includes a positive electrode active material and a negative electrode active material; wherein the positive electrode active material is selected from at least one of lithium iron phosphate, lithium manganese iron phosphate, lithium nickel cobalt manganese oxide, lithium cobalt oxide, lithium manganese oxide, lithium nickel cobalt aluminum oxide and manganese dioxide; the negative electrode active material is selected from at least one of artificial graphite, natural graphite, lithium titanate, silicon oxygen negative electrode material and silicon carbon. The preparation method of the electrode film of the present application is applicable to positive electrode films and negative electrode films, and other types of positive electrode active materials, negative electrode active materials or conductive agents can also be selected according to actual needs.

[0070] The conductive agent of the present application mainly uses carbon nanotubes (CNT) and graphite. Since carbon nanotubes and PTFE fibers have similar one-dimensional linear morphologies, the two may produce a synergistic effect and can connect more active material particles, thereby building a more effective electron flow network. The role of graphite is that its lamellar structure has good lubricity, which can help the powder film thinning process.

[0071] According to a second aspect of the present application, a dry electrode membrane is provided, which is prepared by using the above-mentioned method for preparing the dry electrode membrane.

[0072] In some embodiments, the thickness of the dry electrode film is 100-152 μm, for example, 115-152 μm; the tensile strength is 0.15-0.4 MPa, for example, 0.15-0.30 MPa; for example, 0.15-0.25; the compaction density is 2.50-3.30 g / cm 3 , for example 2.50~3.0g / cm 3 .

[0073] The electrode membrane prepared by the method of the present application has good PTFE dispersion, good uniformity, and high degree of fiberization, which improves the mechanical properties such as tensile strength of the electrode membrane, increases the compaction density of the electrode membrane, and thus increases the energy density of the battery; this method is also suitable for thicker electrode membranes.

[0074] According to the third aspect of the present application, a method for preparing a dry electrode is provided, and the method for preparing a dry electrode comprises the following steps: rolling a dry electrode film onto at least one side of a current collector; wherein the dry electrode film is the above-mentioned dry electrode film.

[0075] In some embodiments, the rolling temperature when applying the current collector is 0°C to 100°C; the current collector is selected from at least one of copper foil, carbon-coated copper foil, aluminum foil, nickel foil, stainless steel mesh, aluminum mesh and nickel mesh.

[0076] The electrode film prepared by the method of the present application can be coated on one side or both sides of the positive electrode current collector or the negative electrode current collector, and the current collector can be selected from other types according to actual needs.

[0077] According to a fourth aspect of the present application, a battery is provided, comprising an electrode, a separator and an electrolyte; the electrode is an electrode prepared by the above-mentioned dry electrode preparation method.

[0078] The present application is further described in detail below in conjunction with specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed in the present application.

[0079] All raw materials and equipment used in the examples of this application are prior art and can be purchased commercially.

[0080] Example 1

[0081] The preparation process of battery electrodes is as follows Figure 1 As shown, the following steps are included:

[0082] (1) PTFE insulation: The secondary particle size of PTFE is 570 μm, the molecular weight is 7.7 million, and the compression ratio is 100-300; the PTFE is placed at -10°C and kept warm for 10 hours;

[0083] (2) Premixing: Lithium iron phosphate (LFP), graphite, and carbon nanotubes were mixed uniformly in a ball mill at a ratio of 92:2:3 and a ball-to-material ratio of 1:1 at 500 rpm to obtain powder A. Powder A and the heat-insulated binder PTFE were placed in a double-motion mixer at a ratio of 98:2 and mixed for 30 min to obtain powder B, whose average particle size was 10.4 μm. The morphology of the PTFE-coated active material after mixing is as follows: Figure 2 As shown;

[0084] (3) Fiberization: Powder B was ground with low-temperature airflow using an airflow grinder at an airflow temperature of 0°C, a grinding pressure of 0.70 MPa, and a classifying wheel speed of 10,000 rpm to obtain powder C with an average particle size of 3.6 μm. The effect of PTFE fiberization is as follows: Figure 3 As shown;

[0085] The powder C was then ground with a jet mill at high temperature, with the air flow temperature at 80°C, the grinding pressure at 0.90 MPa, and the classifying wheel speed at 10000 rpm, to obtain powder D.

[0086] (4) Film formation: The powder D was subjected to fiberization and film formation using a multi-stage differential speed roller press. The speed ratio of the roller press was 1:1.5, and the temperature was 120°C / 100°C / 60°C. Each roller press was performed once to obtain an electrode film with a thickness of 120 μm, a tensile strength of 0.25 MPa, and a compaction density of 2.90 g / cm 3 The morphology of the membrane is as follows Figure 4 As shown;

[0087] (5) Coating the current collector: After the film is formed, it is rolled onto both sides of the aluminum foil current collector to form electrodes at a rolling temperature of 50°C to obtain a positive electrode sheet.

[0088] Example 2

[0089] The difference between Example 2 and Example 1 is that the fiberization process in step (3) is different;

[0090] Fiberization: Powder B was ground by low-temperature airflow grinding in an airflow grinder, with an airflow temperature of -10°C, a grinding pressure of 0.80 MPa, and a classifying wheel speed of 10000 rpm to obtain powder C, whose average particle size was 4.1 μm;

[0091] The powder C was then ground with a jet mill at high temperature, with the air flow temperature at 90°C, the grinding pressure at 0.90 MPa, and the classifying wheel speed at 10,000 rpm to obtain powder D|.

[0092] Example 3

[0093] Example 3 The difference between Example 1 and Example 1 is that the fiberization process in step (3) is different;

[0094] Fiberization: Powder B was ground with low-temperature airflow using an airflow grinder (model), with an airflow temperature of -5°C, a grinding pressure of 0.90 MPa, and a classifying wheel speed of 10000 rpm to obtain powder C, whose average particle size was 3.2 μm;

[0095] The powder C was then ground with a jet mill at high temperature, with the air flow temperature at 100°C, the grinding pressure at 0.90 MPa, and the classifying wheel speed at 10,000 rpm to obtain powder D.

[0096] Example 4

[0097] The difference between Example 4 and Example 1 is that the fiberization process in step (3) is different;

[0098] Fiberization: Powder B was ground by low-temperature air flow grinding in an air flow grinder at an air flow temperature of 5°C, a grinding pressure of 0.90 MPa, and a classifying wheel speed of 10,000 rpm to obtain powder C with an average particle size of 4.0 μm.

[0099] The powder C was then ground with a jet mill at high temperature at an air flow temperature of 70°C, a grinding pressure of 0.90 MPa, and a classifying wheel speed of 10,000 rpm to obtain powder D.

[0100] Example 5

[0101] The difference between Example 5 and Example 1 is that the fiberization process in step (3) is different;

[0102] Fiberization: Powder B was ground with low-temperature airflow using an airflow grinder at an airflow temperature of 10°C, a grinding pressure of 0.90 MPa, and a classifying wheel speed of 10,000 rpm to obtain powder C with an average particle size of 3.5 μm.

[0103] The powder C was then ground with a jet mill at high temperature, with the air flow temperature at 60°C, the grinding pressure at 0.90 MPa, and the classifying wheel speed at 10,000 rpm to obtain powder D.

[0104] Example 6

[0105] The difference between Example 6 and Example 1 is that the fiberization process in step (3) is different;

[0106] Fiberization: Powder B was ground by low-temperature airflow grinding in an airflow grinder, with an airflow temperature of 3°C, a grinding pressure of 0.90 MPa, and a classifying wheel speed of 10000 rpm to obtain powder C with an average particle size of 3.9 μm;

[0107] The powder C was then ground with a jet mill at high temperature, with the air flow temperature at 50°C, the grinding pressure at 0.90 MPa, and the classifying wheel speed at 10,000 rpm to obtain powder D.

[0108] Example 7

[0109] The difference between Example 7 and Example 1 is that the fiberization process in step (3) is different;

[0110] Fiberization: Powder B was ground by low-temperature airflow grinding in an airflow grinder, with an airflow temperature of 0°C, a grinding pressure of 0.70 MPa, and a classifying wheel speed of 8000 rpm to obtain powder C, whose average particle size was 5.4 μm;

[0111] The powder C was then ground with a jet mill at high temperature, with the air flow temperature at 80°C, the grinding pressure at 0.90 MPa, and the classifying wheel speed at 8000 rpm to obtain powder D.

[0112] Example 8

[0113] The difference between Example 8 and Example 1 is that the fiberization process in step (3) is different;

[0114] Fiberization: Powder B was ground by low-temperature airflow grinding in an airflow grinder, with an airflow temperature of 0°C, a grinding pressure of 0.70 MPa, and a classifying wheel speed of 9000 rpm to obtain powder C with an average particle size of 6.1 μm;

[0115] The powder C was then ground with a jet mill at high temperature at an air flow temperature of 80°C, a grinding pressure of 0.90 MPa, and a classifying wheel speed of 9000 rpm to obtain powder D.

[0116] Example 9

[0117] The difference between Example 9 and Example 1 is that the fiberization process in step (3) is different;

[0118] Fiberization: Powder B was ground by low-temperature airflow grinding in an airflow grinder, with an airflow temperature of 0°C, a grinding pressure of 0.70 MPa, and a classifying wheel speed of 11000 rpm to obtain powder C with an average particle size of 5.0 μm;

[0119] The powder C was then ground with a jet mill at high temperature, with the air flow temperature at 80°C, the grinding pressure at 0.90 MPa, and the classifying wheel speed at 11000 rpm to obtain powder D.

[0120] Example 10

[0121] The difference between Example 10 and Example 1 is that the fiberization process in step (3) is different;

[0122] Fiberization: Powder B was ground by low-temperature airflow grinding in an airflow grinder, with an airflow temperature of 0°C, a grinding pressure of 0.70 MPa, and a classifying wheel speed of 12000 rpm to obtain powder C with an average particle size of 4.7 μm;

[0123] The powder C was then ground with a jet mill at high temperature, with the air flow temperature at 80°C, the grinding pressure at 0.90 MPa, and the classifying wheel speed at 12000 rpm to obtain powder D.

[0124] Embodiment 11

[0125] The difference between Example 11 and Example 1 is that the fiberization process in step (3) is different;

[0126] Fiberization: Powder B was ground by low-temperature airflow grinding in an airflow grinder, with an airflow temperature of 0°C, a grinding pressure of 0.70 MPa, and a classifying wheel speed of 10000 rpm to obtain powder C with an average particle size of 5.6 μm;

[0127] The powder C was then ground with a jet mill at high temperature at an air flow temperature of 90°C, a grinding pressure of 0.90 MPa, and a classifying wheel speed of 12000 rpm to obtain powder D.

[0128] Example 12

[0129] The difference between Example 12 and Example 1 is that the active material in step (2) is a negative electrode active material;

[0130] Premixing: artificial graphite and carbon nanotubes were mixed in a ball mill at a ratio of 92:6 and a ball-to-material ratio of 1:1 at 500 rpm to obtain powder A. Powder A and the heat-insulated binder PTFE were placed in a double-motion mixer at a ratio of 98:2 and mixed for 30 minutes to obtain powder B.

[0131] Comparative Example 1

[0132] The difference between Comparative Example 1 and Example 1 is that the PTFE is not subjected to low-temperature high-speed grinding and shearing treatment, but directly subjected to high-temperature airflow grinding and fiberization;

[0133] (3) Fiberization: Powder B was fiberized by high-temperature air flow grinding in an air flow grinder at an air flow temperature of 80°C, a grinding pressure of 0.90 MPa, and a classifying wheel speed of 10,000 rpm to obtain powder D.

[0134] Comparative Example 2

[0135] The difference between Comparative Example 2 and Example 1 is that in step (3), the powder C is fiberized at room temperature;

[0136] The powder C was jet-milled using a jet mill at an air flow temperature of 20° C., a grinding pressure of 0.90 MPa, and a classifying wheel speed of 10,000 rpm to obtain powder D.

[0137] Comparative Example 3

[0138] The difference between Comparative Example 3 and Example 1 is that the PTFE content in step (1) is 8 wt % and in step (3) the PTFE is not subjected to low-temperature high-speed grinding and shearing treatment but is subjected to room-temperature fiberization;

[0139] Lithium iron phosphate (LFP), graphite, and carbon nanotubes were mixed uniformly in a ball mill at a ratio of 90:1:1 at 500 rpm to obtain powder A. Powder A and the heat-insulated binder PTFE were placed in a double-motion mixer at a ratio of 90:8 and mixed for 30 minutes to obtain powder B.

[0140] The powder B was subjected to air flow grinding and fiberization in a low-temperature air flow grinder at an air flow temperature of 20°C, a grinding pressure of 0.90 MPa, and a classifying wheel speed of 10,000 rpm to obtain powder D.

[0141] Comparative Example 4

[0142] The difference between Comparative Example 4 and Example 1 is that in step (3), the PTFE is not subjected to low-temperature high-speed grinding and shearing treatment, but fiberization is performed at room temperature;

[0143] The powder B was ground by low-temperature air flow grinding in an air flow grinder at an air flow temperature of 20°C, a grinding pressure of 0.90 MPa, and a classifying wheel speed of 10000 rpm to obtain powder D.

[0144] Comparative Example 5

[0145] The difference between Comparative Example 5 and Example 1 is that the temperature at which the powder B is subjected to airflow grinding and shearing in step (3) is different;

[0146] The powder B was ground by low-temperature air flow grinding in an air flow grinder at an air flow temperature of 15°C, a grinding pressure of 0.70 MPa, and a classifying wheel speed of 10000 rpm to obtain powder C.

[0147] Comparative Example 6

[0148] The difference between Comparative Example 6 and Example 1 is that the temperature at which the powder B is subjected to airflow grinding and shearing in step (3) is different;

[0149] The powder B was ground by low-temperature air flow grinding in an air flow grinder at an air flow temperature of 19° C., a grinding pressure of 0.70 MPa, and a classifying wheel speed of 10,000 rpm to obtain powder C.

[0150] The thickness, tensile strength and compacted density of the electrode films prepared in Examples 1 to 12 and Comparative Examples 1 to 6 were tested; the tensile strength test method referred to "GB / T 1040.2-2022 Determination of Tensile Properties of Plastics" Part 2: Test Conditions for Molded and Extruded Plastics; the test results are shown in Table 1.

[0151] Electrochemical performance testing method: Use Yuanneng Technology BER2300 electrode resistor meter to test the resistivity of the obtained electrode film.

[0152] The test method for liquid absorption rate is: take a 10ⅹ3cm membrane and weigh it, recorded as the front weight m1. After weighing, soak the membrane in electrolyte for 2 hours, then use tweezers to remove and wipe off the free electrolyte on the surface, and weigh it, recorded as m2. The liquid absorption rate = (m2-m1) / m1.

[0153] The resistivity and liquid absorption rate of the prepared electrode were tested using the above method.

[0154] Table 1

[0155]

[0156] The test data in Table 1 show that the electrode film prepared by the dry process of Examples 1 to 12 of the present application has a thickness of 115 to 152 μm, a tensile strength of 0.15 to 0.22 MPa, and a compaction density of 2.65 to 2.90 g / cm 3 (Example 12 is a negative electrode with a compaction density of 1.76); tensile strength, resistivity, and liquid absorption rate are as follows Figure 5 , Figure 6 , Figure 7 and Figure 8 shown.

[0157] In the preparation method of Comparative Example 1, PTFE was not subjected to low-temperature high-speed grinding and shearing first, but the micron-sized PTFE and the nano-sized active material and conductive agent were mixed and then directly subjected to high-temperature airflow grinding. Due to the poor dispersibility and unevenness of the PTFE mixture, the fiberization effect was even worse. The tensile strength of the electrode film prepared was 0.14MPa; the compaction density was 2.78g / cm 3 , the electrode membrane is prone to cracking or breaking, and there is obviously unevenly dispersed PTFE on the membrane surface. By comparison, it can be seen that the present application can significantly promote the uniformity of PTFE dispersion and better fiberization effect by first making PTFE into nano-sized particles under low-temperature and high-speed grinding and shearing conditions, and then performing high-temperature and high-speed grinding and shearing fiberization treatment, and the tensile strength of the prepared membrane is significantly improved.

[0158] In Comparative Example 2, PTFE was fiberized at room temperature. However, due to the inappropriate fiberization temperature, a continuous electrode membrane could not be obtained, and the membrane was interrupted during thinning. This indicates that in order to obtain a better fiberization effect when fiberizing PTFE, the fiberization temperature must reach a certain value.

[0159] In Comparative Example 3, the PTFE content is too high, the PTFE is not subjected to low-temperature high-speed shearing, and fiberization is performed at room temperature; cracks are formed during the thinning process of the diaphragm, which greatly reduces the tensile strength of the diaphragm.

[0160] In Comparative Example 4, PTFE was not subjected to low-temperature high-speed grinding and shearing treatment and fiberization was performed at room temperature; during the film-forming process, the powder meshed and stuck, and had no tensile strength.

[0161] Comparative Examples 5 and 6 use a temperature close to the phase transition temperature of PTFE for low-temperature airflow grinding. At this temperature, part of the PTFE has been fibrosed due to the heat generated by the shearing process in the process of making nano-sized particles from micron-sized particles, which will hinder and destroy the effect of PTFE making nano-sized particles, resulting in poor dispersion and uniformity of the final PTFE, making the PTFE fiber effect poor, thereby reducing the tensile strength of the diaphragm. By comparison, it can be seen that before PTFE is fibrosed, not only must PTFE be made into nano-sized particles, but also the situation that PTFE is fibrosed in advance due to excessively high shearing temperatures in the process of making nano-sized particles must be avoided. Therefore, when PTFE is made into nano-sized particles, the shearing temperature of the process must be strictly controlled.

[0162] like Figure 7 As shown, the resistivity of the electrode sheet represented by Example 1 is the smallest, at 9 mΩ, the resistivity of the electrode sheet of Comparative Example 3 is the largest, and the resistivity of the electrode sheets of Comparative Examples 2 and 3 is at least 2 times higher than that of Example 1. It is explained that after the PTFE is first subjected to low-temperature high-speed grinding and shearing to reach the nanometer level in Example 1 of the present application, the resistivity of the electrode prepared is only about 30% of the resistivity of the electrode prepared by using micron-grade PTFE.

[0163] like Figure 8 As shown, the liquid absorption rate of the electrode sheet represented by Example 1 is the largest, reaching more than 225%, and the liquid absorption rates of the electrode sheets of Comparative Examples 1, Comparative Examples 2, and Comparative Examples 3 decrease in turn, and the liquid absorption rate of Comparative Example 1 is only about 65% of that of Example 1. It is explained that the liquid absorption rate of the electrode prepared by Example 1 of the present application is increased by more than 35% by grinding and shearing PTFE at low temperature and high speed to reach the nanometer level than that of the electrode prepared directly using micron-grade PTFE.

[0164] The above description shows that the tensile strength, compaction density, etc. of the dry electrode membrane prepared by the method of the present application can be significantly improved, and the resistivity of the dry electrode can be significantly reduced, and the liquid absorption rate can be improved.

[0165] It should be noted that the terms "first", "second", etc. in the specification and claims of the present application are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequence. It should be understood that the terms used in this way can be interchangeable where appropriate, so that the embodiments of the present application described herein can be implemented in an order other than those described herein, for example.

[0166] The above description is only an embodiment of the present application and is not intended to limit the present application. For those skilled in the art, the present application may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.

Claims

1. A method for preparing a dry electrode membrane, characterized in that: The method comprises the following steps: Step S1: mixing and crushing a polytetrafluoroethylene material, an electrode active material and a conductive agent to obtain a crushed mixture; Step S2: performing air flow grinding and shearing on the pulverized mixed material to obtain a ground and sheared mixed material; wherein the conditions of the air flow grinding and shearing include: an air flow temperature of -10°C to 10°C, a compressed air flow pressure of 0.7 to 0.9 MPa, and a shearing speed of 8000 to 12000 rpm; Step S3: performing secondary airflow grinding and shearing fiberization on the ground and sheared mixture to obtain a fiberized material; Step S4: performing secondary fiberization treatment on the fiberized material to obtain a dry electrode membrane.

2. The method for preparing a dry electrode membrane according to claim 1, characterized in that: The air flow temperature of the primary air flow grinding and shearing is -5°C to 5°C, preferably 0 to 5°C; And / or, the conditions of the secondary airflow grinding and shearing include: airflow temperature of 50°C to 100°C, compressed airflow pressure of 0.7 to 0.9 MPa, and shearing speed of 8000 to 12000 rpm; Preferably, the air flow temperature of the secondary air flow grinding and shearing is 60-100°C; preferably 70-100°C; more preferably 80-100°C; the shearing speed is 10000-11000rpm; And / or, the shearing speed of the primary air flow grinding and shearing is 10000-11000 rpm; And / or, the polytetrafluoroethylene material is a polytetrafluoroethylene dispersion resin, having an average particle size of 400-600 μm, a molecular weight of 500,000-8 million, and a compression ratio of 100-3000; Preferably, the polytetrafluoroethylene dispersion resin is kept at -8°C to -12°C for 8 to 12 hours before mixing.

3. The method for preparing a dry electrode membrane according to claim 2, characterized in that: The specific process of step S1 includes: mixing and crushing the electrode active material and the conductive agent to obtain powder A; mixing and crushing the heat-insulated polytetrafluoroethylene dispersion resin and the powder A to obtain the crushed mixture; Preferably, the electrode active material and the conductive agent are mixed by a ball mill or a high-speed mixer, and the rotation speed of the high-speed mixer is 400 to 600 rpm; Preferably, the ball-to-material ratio of the ball mill is 1:(1-2); Preferably, the polytetrafluoroethylene dispersion resin and the powder A are mixed using a double-motion mixer or a three-dimensional motion mixer; Preferably, the mixing time of the polytetrafluoroethylene dispersion resin and the powder A in the double-motion mixer is 20 to 40 minutes.

4. The method for preparing a dry electrode membrane according to any one of claims 1 to 3, characterized in that: The average particle size of the pulverized mixture is 8 to 12 μm; and / or, the average particle size of the ground and sheared mixture is 3 to 6 μm; And / or, the primary air flow grinding and shearing and / or the secondary air flow grinding and shearing adopts an air flow grinder; Preferably, the air flow mill is a fluidized bed air flow mill.

5. The method for preparing a dry electrode membrane according to any one of claims 1 to 4, characterized in that: The secondary fiberization treatment uses a differential speed roller press to perform differential speed fiberization; Preferably, the rolling temperature of the differential speed roller press is 60° C. to 120° C., and the rolling speed ratio is 1:(1 to 1.5).

6. The method for preparing a dry electrode membrane according to any one of claims 2 to 5, characterized in that: The weight ratio of the electrode active material to the conductive agent is (90-95): (0~5); and / or, the weight ratio of the powder A to the polytetrafluoroethylene dispersion resin after heat preservation is (95-99):(1-5); And / or, the electrode active material includes a positive electrode active material and a negative electrode active material; wherein the positive electrode active material is selected from at least one of lithium iron phosphate, lithium manganese iron phosphate, lithium nickel cobalt manganese oxide, lithium cobalt oxide, lithium manganese oxide, lithium nickel cobalt aluminum oxide and manganese dioxide; the negative electrode active material is selected from at least one of artificial graphite, natural graphite, lithium titanate, silicon oxygen negative electrode material and silicon carbon; And / or, the conductive agent is selected from at least one of conductive carbon black, graphite, graphene, carbon nanotubes, carbon fibers, acetylene black and Ketjen black.

7. A dry electrode membrane, characterized in that: The dry electrode membrane is prepared by the method for preparing a dry electrode membrane according to any one of claims 1 to 6.

8. The dry electrode membrane according to claim 7, characterized in that: The thickness of the dry electrode film is 100-152 μm, the tensile strength is 0.15-0.4 MPa, and the compaction density is 2.50-3.30 g / cm 3 .

9. A method for preparing a dry electrode, characterized in that: The preparation method of the dry electrode comprises the following steps: rolling a dry electrode film onto at least one side of a current collector; wherein the dry electrode film is the dry electrode film according to claim 7 or 8; Preferably, the temperature of the rolling is 0°C to 100°C; Preferably, the current collector is selected from at least one of copper foil, carbon-coated copper foil, aluminum foil, nickel foil, stainless steel mesh, aluminum mesh and nickel mesh.

10. A battery comprising an electrode, a separator and an electrolyte; characterized in that: The electrode is an electrode prepared by the dry electrode preparation method according to claim 9.

Citation Information

Patent Citations

  • Preparation method of dry-method pole piece

    CN114725320A

  • Method for preparing electrode membrane of lithium ion battery by dry method

    CN115579458A

  • Dry-method battery material mixing method and dry electrode diaphragm preparation method

    CN116031360A

  • Method for preparing positive pole piece by dry method, positive pole piece and battery

    CN116364846A

  • Method for preparing silicon-carbon negative electrode and silicon-carbon battery by dry method

    CN116646469A

Cited By

  • Dry-method electrode and preparation method and application thereof

    CN119965224A

  • Mixing method of electrode material, preparation method of electrode diaphragm, battery pole piece, battery and electronic equipment

    CN120545297A

  • Lithium-manganese button cell positive electrode ring prepared based on dry electrode process as well as preparation method and application of lithium-manganese button cell positive electrode ring

    CN121076057A

  • A positive electrode ring of lithium-manganese button cell prepared based on dry electrode process and a preparation method and application thereof

    CN121076057B

  • Multistage fiberized dry-method pole piece, preparation method thereof and battery

    CN121439710A